An Adaptive All-odd transformation Watermark Scheme - Qiaomei Ma; Lijun Wu; Jianhong Du; Gouxi Chen; Qiuxiang Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Combining discrete wavelet transform, human visual system, chaotic map and odd-even quantization, a novel watermarking scheme for 2D images is proposed in this paper. Encrypted watermarking and identity information are imperceptibly embedded in 2D images according to this scheme. For improving the accuracy of just noticeable distortion and enhance robustness of algorithm, the model adaptively adjusts the threshold intensity by adding weighting factor and strengthening the brightness sensitivity calculation method of just noticeable distortion. The bijection relationship is constructed between the image coefficients and watermarking bits by the way of all-odd transformation to the just noticeable distortion, so the scheme realizes blind extraction of watermark. The experimental results and analysis show that the proposed scheme can resist intentional or unintentional variety of attacks and have superiority comparing with existing schemes. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4228